2009
DOI: 10.1002/qj.406
|View full text |Cite
|
Sign up to set email alerts
|

A Gill–Matsuno‐type mechanism explains the tropical Atlantic influence on African and Indian monsoon rainfall

Abstract: Recent studies using coupled atmosphere-ocean models have shown that the tropical Atlantic has a significant impact on the Indian monsoon. In this article, the observational basis for this teleconnection is examined and the physical mechanism responsible for bridging sea-surface temperatures (SSTs) in the Atlantic and precipitation over India is investigated with idealized atmospheric general circulation model (AGCM) experiments in which constant SST anomalies are prescribed and 'switched on' in the tropical A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
170
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(189 citation statements)
references
References 47 publications
14
170
1
Order By: Relevance
“…This allows us to compare our results, obtained for a glacial base state, with similar experiments run to study the present-day monsoon variability (e.g. Kucharski et al, 2009). We then investigate if the relationship we find between tropical SST changes and those in Indian monsoon precipitation holds in additional coupled model experiments in which we force the AMOC to recover.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…This allows us to compare our results, obtained for a glacial base state, with similar experiments run to study the present-day monsoon variability (e.g. Kucharski et al, 2009). We then investigate if the relationship we find between tropical SST changes and those in Indian monsoon precipitation holds in additional coupled model experiments in which we force the AMOC to recover.…”
Section: Introductionmentioning
confidence: 72%
“…They show that if the ENSO (El Niño Southern Oscillation)-forced variability is subtracted, the strong Indian monsoon years correspond to cold south equatorial Atlantic sea-surface temperatures (SSTs). Kucharski et al (2009) and Losada et al (2010) also highlight the teleconnection between the tropical Atlantic and the Indian monsoon circulation at shorter timescales. By using an atmospheric general circulation model to perform sensitivity experiments to SST anomalies in the north and the south tropical Atlantic, they find the south tropical Atlantic sea-surface temperatures to be determinant in the variations of the Indian monsoon.…”
Section: Introductionmentioning
confidence: 92%
“…Computationally, SPEEDY is 1 order of magnitude faster than a state-of-the-art AGCM at the same horizontal resolution, whereas the quality of the simulated climate and patterns of variability in the free atmosphere compare well with these models and with observations (Hazeleger et al, 2003;Molteni, 2003). Various studies with SPEEDY have demonstrated its ability to simulate the dominant responses to surface anomalies Bracco et al, 2007;Haarsma and Hazeleger, 2007;Kucharski et al, 2007Kucharski et al, , 2008Sterl et al, 2007;Kucharski et al, 2009). It is therefore suitable for studies on climate-vegetation feedbacks and inter-decadal or inter-centennial variability.…”
Section: Methodsmentioning
confidence: 98%
“…We examine these issues in the International Centre for Theoretical Physics climate model (27,28), which has been used for a number of climate problems (29,30). Here a triangular truncation at total wavenumber 30 (T30) version is used, roughly equivalent to a 3.75°× 3.75°spatial resolution.…”
Section: Climate Model Setupmentioning
confidence: 99%